Electronic properties of single-crystalline Fe4O5. Issue 17 (4th April 2023) - Ovsyannikov, Sergey V.; Karkin, Alexander E.; Korobeinikov, Igor V.; Morozova, Natalia V.; Bykov, Maxim; Bykova, Elena; Dubrovinsky, Leonid
Abstract : We synthesized single crystals of Fe4 O5 under high-pressure high-temperature conditions. At ambient conditions they demonstrated a semimetal electrical conductivity with nearly equal partial contributions of electrons and holes. Abstract : We synthesized single and polycrystals of iron oxide with an unconventional Fe4 O5 stoichiometry under high-pressure high-temperature (HP–HT) conditions. The crystals of Fe4 O5 had a CaFe3 O5 -type structure composed of linear chains of iron with octahedral and trigonal-prismatic oxygen coordinations. We investigated the electronic properties of this mixed-valence oxide using several experimental techniques, including measurements of electrical resistivity, the Hall effect, magnetoresistance, and thermoelectric power (Seebeck coefficient), X-ray absorption near edge spectroscopy (XANES), reflectance and absorption spectroscopy, and single-crystal X-ray diffraction. Under ambient conditions, the single crystals of Fe4 O5 demonstrated a semimetal electrical conductivity with nearly equal partial contributions of electrons and holes ( σ n ≈ σ p ), in line with the nominal average oxidation state of iron as Fe 2.5+ . This finding suggests that both the octahedral and trigonal-prismatic iron cations contribute to the electrical conductivity of Fe4 O5 via an Fe 2+ /Fe 3+ polaron hopping mechanism. A moderate deterioration of crystal quality shifted the dominant electrical conductivity to n-type and considerably worsened the conductivity. Thus, alike magnetite, Fe4 O5 with equal numbers of Fe 2+ and Fe 3+ ions can serve as a prospective model for other mixed-valence transition-metal oxides. In particular, it could help in the understanding of the electronic properties of other recently discovered mixed-valence iron oxides with unconventional stoichiometries, many of which are not recoverable to ambient conditions; it can also help in designing novel more complex mixed-valence iron oxides.